Measuring Employment Readiness for Hard-to-Place Individuals - Simon Tranberg Bodilsen; Søren Albeck Nielsen; Michael Rosholm (Institute of Labor Economics (IZA), 2023)
In an era characterized by population aging and economic challenges in welfare states across the world, sustaining these welfare systems requires a large workforce. Many individuals outside the labor market aspire to work but encounter a labyrinth of obstacles. While Public Employment Services employ Active Labor Market Policies, their effectiveness for this group remains uncertain. This study introduces the Employment Readiness Indicator Questionnaire (ERIQ), transcending traditional employment categories by assessing individuals' progress toward employment and measuring employment readiness for those labeled "hard-to-place". Integrating socially vulnerable clients into the labor market remains an unsolved challenge. ERIQ demonstrates impressive predictive abilities and points towards actionable recommendations by identifying malleable traits, such as social skills, coping strategies, goal orientation, and self-efficacy, that significantly impact employment readiness. ERIQ emerges as a valuable resource for policymakers and practitioners, advancing the goal of promoting labor market participation for socially vulnerable individuals.
Keywords: J60; J64; J68; 330; employment readiness; social assistance; machine learning; predictive algorithms